2020
DOI: 10.1007/s13233-020-8109-x
|View full text |Cite
|
Sign up to set email alerts
|

Porous Poly(3-hydroxybutyrate) Scaffolds Prepared by Non-Solvent-Induced Phase Separation for Tissue Engineering

Abstract: Highly porous poly(3-hydroxybutyrate) (PHB) scaffolds were fabricated using non-solvent-induced phase separation with chloroform as the solvent and tetrahydrofuran as the non-solvent. The microporosity, nanofiber morphology, and mechanical strength of the scaffolds were adjusted by varying the fabrication parameters, such as the polymer concentration and solvent composition. The influence of these parameters on the structure and morphology of PHB organogels and scaffolds was elucidated using small-angle neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 53 publications
(93 reference statements)
0
13
0
Order By: Relevance
“…In the end, the in vivo osteogenesis and the vascular formation were significantly promoted in scaffolds with DFO loading. In Kang’s study, highly porous poly(3-hydroxybutyrate) (PHB) scaffolds were fabricated using nonsolvent-induced phase separation followed by freeze-drying under 30 mTorr at −130 °C for 2 days [ 21 ]. The scaffolds showed well-connected micropores with increasing nonsolvent content and porosity in the range of 97 to 99%.…”
Section: Combination Of Solution-based Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end, the in vivo osteogenesis and the vascular formation were significantly promoted in scaffolds with DFO loading. In Kang’s study, highly porous poly(3-hydroxybutyrate) (PHB) scaffolds were fabricated using nonsolvent-induced phase separation followed by freeze-drying under 30 mTorr at −130 °C for 2 days [ 21 ]. The scaffolds showed well-connected micropores with increasing nonsolvent content and porosity in the range of 97 to 99%.…”
Section: Combination Of Solution-based Techniquesmentioning
confidence: 99%
“…Generally, the choice of the material for solution-based technologies relies on the desired morphology, function, and application of the produced scaffold, including biopolymers such as polycaprolactone (PCL) [ 9 , 10 ], polylactide (PLA) [ 11 , 12 , 13 ], poly(lactide-co-glycolide; PLGA) [ 14 ], poly(vinyl) alcohol (PVA) [ 15 ], gelatin [ 16 ], chitosan [ 10 ], and collagen [ 17 , 18 ]. According to the expected structural and mechanical performance for tissue replacement, different solution-based fabrication methods could be applied ( Figure 1 ), such as freeze-drying [ 17 , 19 , 20 ] ( Figure 1 a), Thermally or Diffusion Induced Phase Separation (TIPS ( Figure 1 b) or DIPS ( Figure 1 c)) [ 21 , 22 ], electrospinning [ 23 , 24 ] ( Figure 1 d), or a valuable combination of them [ 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in similar applications for skin engineering, the fiber matrices based on PHBV and obtained by electrospinning demonstrated that human skin fibroblasts (CRL 2072) were able to adhere and colonize these new substrates [44]. Different PHB organogels and scaffolds with complex hierarchical structure and covering a wide range of length scales have been prepared by TIPS and showed an excellent cell viability using the human keratinocyte cell line (HaCaT) [46]. Finally, our results contribute to the suggestion of the great application of PHBV in tissue engineering.…”
Section: Biocompatibility Of Porous Phbv Scaffoldsmentioning
confidence: 99%
“…Biomimetic cellular environments can be produced from the synthesis of polyhydroxyalkanoate (PHA) scaffolds (1). Poly (3-hydroxybutyrate) [PHB] is a PHA frequently used for producing new biocompatible materials, with many physicochemical characteristics relevant for biomedical applications, and it has been combined with diverse materials to prepare scaffolds that support cell proliferation (2)(3)(4). Due to its excellent biodegradability and biocompatibility properties, chitosan (CS) grafted (g) onto PHB appears to be a viable option to produce scaffolds that maintain cell growth (5,6).…”
Section: Introductionmentioning
confidence: 99%